2018
DOI: 10.1373/clinchem.2017.277905
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Serum and Plasma by Quantification of (4E,14Z)-Sphingadienine-C18-1-Phosphate Uncovers Common Preanalytical Errors During Handling of Whole Blood

Abstract: BACKGROUND:Nonadherence to standard operating procedures (SOPs) during handling and processing of whole blood is one of the most frequent causes affecting the quality of serum and plasma. Yet, the quality of blood samples is of the utmost importance for reliable, conclusive research findings, valid diagnostics, and appropriate therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…The presence of SPD in the plasma, lymph, brain, and lungs of humans and/or mice has been reported . However, the process of characterizing SPD has been slower than that of other sphingoid bases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of SPD in the plasma, lymph, brain, and lungs of humans and/or mice has been reported . However, the process of characterizing SPD has been slower than that of other sphingoid bases.…”
Section: Introductionmentioning
confidence: 99%
“…20 The presence of SPD in the plasma, lymph, brain, and lungs of humans and/or mice has been reported. [21][22][23][24] However, the process of characterizing SPD has been slower than that of other sphingoid bases. Here we reveal the tissue distribution of SPD, the activity of sphingoid base-or sphingoid-base 1-phosphate-metabolizing enzymes toward SPD/ SPD 1-phosphate (SPD1P), the enzyme involved in SPD biosynthesis, the synthetic pathway of SPD, and the lipid microdomain localization of SPD-containing sphingolipids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Potential markers for sample quality have been studied using proteomics and metabolomics approaches (Anton et al 2015) (Kong et al 2017). Recently, Liu et al identified (4E,14Z)-sphingadienine-C18-1-phosphate as a biomarker that reflects deviations from SOPs during sample processing and can be used for assessing the quality of serum and plasma samples (Liu et al 2018). To the best of our knowledge no biomarkers for assessing the quality of tissue samples have so far been reported.…”
Section: Quality Control Measuresmentioning
confidence: 99%
“…The correlative research in serum has so far not been widely reported. Nevertheless, accurate quantification of S1P levels in serum still poses many difficulties to modern LC‐MS/MS technology, mainly due to variable effects of a wide variety of biological matrices, as well as the lack of proper matrices free of analytes or samples with known concentrations of analytes …”
Section: Introductionmentioning
confidence: 99%